Erratum: Huet, R.; et al. 1,1-Difluoroethane Detection Time in Blood after Inhalation Abuse Estimated by Monte Carlo PBPK Modeling. Pharmaceutics, 2020, 12, 997 - Raul Huet; Gunnar Johanson (MDPI AG, 2020)
The authors wish to make the following corrections to this paper [...]